A new genus and five new species of the subfamily Florarctinae (Tardigrada, Arthrotardigrada) - Hansen, Jesper G.; Kristensen, Reinhardt M. (European Journal of Taxonomy, 2021)
A new genus Higginsarctus gen. nov. in the subfamily Florarctinae Renaud-Mornant, 1982 (Arthrotardigrada) is established on the basis of the type species H. signeae gen. et sp. nov. described from carbonated sand habitats from Faroe Bank, North Atlantic Ocean. Three other Atlantic species H. laurae gen. et sp. nov., H. martini gen. et sp. nov. and H. shintai gen. et sp. nov. are described from Dentalium sand, Roscoff, France and finally H. lassei gen. et sp. nov. is described from the deep sea in the South Pacific Ocean off the coast of Chile. The recently described species Ligiarctus alatus Gomes-Júnior, E. Santos, da Rocha, P.J.P. Santos & Fontoura, 2018 is investigated and compared with the type species Ligiarctus eastwardi Renaud-Mornant, 1982. New and additional information to the original description of L. alatus is provided and this species is moved to Higginsarctus gen. nov. as H. alatus comb. nov.